FORMULASI DAN UJI AKTIVITAS ANTIOKSIDAN SERUM WAJAH EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) - Abdilla Mahmud Arrafiq; Hasriyani, Hasriyani; Eko Retnowati (Yayasan Nusantara Hasana Berdikari, 2025)
Free radicals accelerate skin aging and cellular damage. Kersen leaves (Muntingia calabura L.) are known to contain flavonoids, saponins, and tannins with antioxidant potential. This study aimed to formulate a facial serum using ethanolic extract of kersen leaves and evaluate its physical properties and antioxidant activity. The extract was obtained via maceration using 96% ethanol and formulated into three concentrations: 5%, 10%, and 15%. Physical evaluations included organoleptic properties, homogeneity, pH, spreadability, viscosity, and irritation tests. Antioxidant activity was assessed using the DPPH method, with IC₅₀ values as indicators. All formulations met the physical quality standards. The 5% extract formula exhibited the highest antioxidant activity with an IC₅₀ value of 72.22 μg/mL, classified as active. Irritation tests confirmed that all formulations were safe for topical use. These findings support the potential of kersen leaf extract as a natural antioxidant ingredient in cosmetic formulations.